Analysis on interaction between solar light and suspended nanoparticles in nanofluids. (July 2021) - Zeng, Jia; Xuan, Yimin
Highlights: Light scattering among nanoparticles in plasmonic, non-plasmon, and hybrid nanofluids are studied. Multiple interactions among nanoparticles enhance photothermal conversion of nanofluids. The interaction features of nanoparticles composed of different materials are explored. Abstract: Nanofluids with efficient solar radiation capture capability show significant benefits in volumetric absorption solar harvesting devices such as solar thermal power generation, solar desalination, and solar water splitting. However, most of the theoretical studies on the radiation characteristics of nanofluids ignore the interaction among nanoparticles, and lack of in-depth analysis on the level of nanoparticles. Only a few studies were involved in the optical interaction among suspended particles made of single materials, but the interactions among the nanoparticles composed of different materials suspended in hybrid nanofluids have not been studied in detail. In this work, to further analyze the light capture mechanism of different nanofluids and guide the design of nanoparticles, we theoretically investigate the optical interaction among nanoparticles in several representative nanofluids, including plasmonic nanofluids, non-plasmon nanofluids, and hybrid nanofluids. In particular, the interactions between different materials in hybrid nanofluids with different combinations are concretely analyzed, and the energy distributions inside the suspended nanoparticles composed of different materials are analyzed. The results show that the optical properties of nanofluids are influenced by the multiple scattering of non-plasmon materials, the near-field radiation enhancement of plasmonic materials, and the secondary concentration of light between two materials. Specially, the photonic nanoparticles combine different materials into one platform can integrate various enhancement effects, which can be applied to solar light capture and functional role at the same time. This work is of great significance of analyzing the application of nanofluids and guiding the design of nanofluids.